2004
DOI: 10.1242/jcs.00991
|View full text |Cite
|
Sign up to set email alerts
|

Trophic signals acting via phosphatidylinositol-3 kinase are required for normal pre-implantation mouse embryo development

Abstract: The growth and survival of the preimplantation mammalian embryo may be regulated by several autocrine trophic factors that have redundant or overlapping actions. One of the earliest trophic factors to be produced is embryo-derived platelet-activating factor (1-O-alky-2-acetyl-sn-glyceryl-3-phosphocholine). The addition of platelet-activating factor to embryo culture media exerted a trophic effect, but structurally related lipids (3-O-alky-2-acetyl-sn-glyceryl-1-phosphocholine, 1-O-alky-sn-glyceryl-3-phosphocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 45 publications
4
51
0
Order By: Relevance
“…This conclusion is in agreement with previous observations that mouse preimplantation embryo development requires PI3K activity from the 8/16-cell stage. 8 If TCL1 is not relevant to AKT phosphorylation in one-cell and two-cell embryos, is this factor needed for the phosphorylated AKT transfer to nucleus? We have addressed this issue by determining the intracellular distribution of Ser473/ Thr308-phosphorylated AKT in two-cell embryos that were genetically deficient in TCL1.…”
Section: P-ser473mentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is in agreement with previous observations that mouse preimplantation embryo development requires PI3K activity from the 8/16-cell stage. 8 If TCL1 is not relevant to AKT phosphorylation in one-cell and two-cell embryos, is this factor needed for the phosphorylated AKT transfer to nucleus? We have addressed this issue by determining the intracellular distribution of Ser473/ Thr308-phosphorylated AKT in two-cell embryos that were genetically deficient in TCL1.…”
Section: P-ser473mentioning
confidence: 99%
“…Embryo exposure to either 10-20 mM LY294002 or 6-24 nM Wortmannin negatively affected preimplantation development from the four-cell stage (Figure 1b), in agreement with previous observations. 8 Interestingly, both inhibitors had no apparent effect on the occurrence of the first embryo cleavage, even when the inhibitor concentration in the medium was raised to extremely high values as 100 mM LY294002 or 100 nM Wortmannin (not shown). Embryos exposed to such high inhibitor concentration displayed an altered overall morphology and did not progress beyond the four-cell stage, indicating that the inhibitor had effectively damaged cellular functions (Supplementary Figure S2a).…”
mentioning
confidence: 94%
“…Murine 2-cell embryos were shown to express the mRNA of multiple PI3-K isoforms including p85a and b and p110 a, b, g, d (Lu et al 2004). In addition, Kawamura et al (2005) demonstrated the presence of p110 transcripts from the oocyte through the hatched blastocysts stage of murine preimplantation development.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al (2004) demonstrated the importance of the PI3-K pathway in mammalian preimplantation embryo development by showing that the activation of PI3-K by an embryonic trophic factor, platelet-activating factor (PAF), is critical for embryo development and survival. PAF treatment of 2-cell embryos results in a transient increase in calcium that is inhibited by both LY-294002 and wortmannin implying that PI3-K activity is required for this PAF-induced biological response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation